COMPARISON OF ARTERIAL PRESSURE AND VASOPRESSOR (PHENYLEPHRINE) AMONG PATIENTS UNDERGOING TURP WITH SPINAL ANESTHESIA VERSUS SADDLE BLOCK - ISLAM, HFU; ASIF, M; ABBAS, A; JAHANGIR, MU; NAJIB, N; SIDDIQUE, MO; FARAZ, A; ASHFAQ, F (Biological and Clinical Sciences Research Journal, 2023)
Transurethral Resection of Prostate (TURP) is a common procedure for treating Benign Prostatic Hyperplasia (BPH) in elderly males. Spinal Anesthesia is conventionally used during the procedure; however, some studies have preferred saddle block regarding the average time of induction requirement for vasopressors. This study compared the mean change in mean arterial pressure and the mean vasopressor requirement (phenylephrine) among patients undergoing TURP with spinal anesthesia versus Saddle block. This randomized controlled trial was conducted at the Anesthesia Department, Jinnah Hospital Lahore, for Six months on 120 cases (group 1: 60, group 2: 60) of male patients aged 40-80 years undergoing TURP surgery. Patients in Group A received 2 ml of 0.75% bupivacaine and were placed supine with one pillow, while Group B received 2 ml of hyperbaric 0.75% in the same manner as Group A but remained in the sitting position for 10 minutes and then made supine with one pillow under the head. Demographic and clinical data was entered and analyzed using SPSS. Mean, Standard Deviation, Frequency, and percentages were calculated for quantitative and qualitative data, respectively, and an independent sample t-test was used for mean differences, keeping p-value<0.05 as significant. The mean age in the Spinal anesthesia group was 61.23 ± 12.06 years, while the mean age in the Saddle block group was 59.55 ± 11.57 years. In the Spinal and Saddle block, the mean arterial pressure before the procedure was 102.60 ± 5.33 and 95.52 ± 4.52, respectively. The mean change in MAP in the spinal group was 20.02 ± 5.76, and in the Saddle block group was 10.95 ± 5.93. The mean vasopressor requirement in Spinal anesthesia was 102.18 ± 19.17, and in Saddle block was 30.67 ± 26.46, respectively. All measures showed significantly lower mean change in Saddle block groups, p-value < 0.05 for all. This study’s findings concluded that the mean change in mean arterial pressure and Vasopressor (phenylephrine) requirement among patients undergoing TURP Saddle block was favorable. So, TURP can be safely performed under saddle block without hypotension and less vasopressor requirement.